Islamic Theology and Extreme Islamist Ideology: Incommensurable Correlation - Zbir, Abdallah (Journal of Humanities & Social Sciences, 2021)
There always exists the lived Islam, the one has been dominating the spheres of religion, politics, society and culture since its formative period; i.e., the one imagined, cut off from critical reason and history and having been used as the basis of authority. This type of Islam, which Mohammed Arkoun refuted, is nothing less than Muslim traditionalists’ Islam – i.e., the one has been developing and growing out their dogmatic readings of revelation and its deterioration into ideologies of dominion. It is the one has been making use of theological (orthodox) doctrines like ‘al-Hakimiyah li Allah’ (no authority but of Allah) not only as the basis of the religious and political elites’ power and control, but also –which is worse – of Islamists extreme ideology. Here, Arkoun notes, such expressions have been taken (still are) as the basis not only of the trueness of Islam, but also of the ideology itself. It all depends on a rigid reading of certain Qur’anic verses. Muslims radicals have always found in them the pretense, arguments; say the justification of their ideology. This research paper attempts, through a critical analytical methodology, to clarify this matter from the viewpoint of Muhammad Arkoun. It lets Arkoun’s ideas circulate through my own analysis, which varies and overlaps following the fluidity of his own methodology. While it does, the comparative mode in it has its own space in certain contexts, which, altogether, form both the theoretical and organizational bases of this paper.
Keywords: Islamic theology; critique; religious authority; theology